A toolkit to facilitate skin research participation in underrepresented ethnic populations: A co‐designed, mixed methods refinement exercise - S. P. Choy; M. Naveed; J. Prasad; K. Quadry; L. Moorhead; C. H. Smith; S. K. Mahil (Wiley, 2024)
Abstract Background Inclusive, generalisable research is vital to inform evidence‐based patient care. However, people from ethnic minority backgrounds remain underrepresented in research, increasing health disparities in under‐served communities. Objectives Codevelop a toolkit to increase the representation of people from ethnic minority groups in skin research. Methods Our four‐phase approach comprised: (1) focus group discussions with individuals from ethnic minority groups with skin diseases to identify barriers and enablers to participate in skin research, (2) a narrative literature review, (3) development of a skin research inclusion toolkit, (4) dissemination of findings. Results Focus group discussions (phase 1) identified a positive value model (belief in the value of research) and inclusive recruitment strategies (e.g. strong patient-recruiter relationships) as enablers to participation. Barriers included mistrust in research (e.g. poor information on personal data use) and social stigma of skin disease. Our narrative literature review (phase 2) reinforced these themes. Social stigma may accentuate feelings of shame or embarrassment associated with a skin condition. Mistrust is accentuated by a lack of information or understanding about research processes. Understanding distinct motivators for research participation across ethnic groups may help to cultivate a positive value model. Inclusive recruitment strategies should be codeveloped with populations of interest and culturally competent research teams to build lasting partnerships. Phases 1‐2 informed a skin research inclusion toolkit (phase 3), which recommends researchers formulate (i) an inclusion plan during study design (e.g. consider differences in pathophysiology of skin diseases across ethnic groups), (ii) inclusive enrolment strategies (e.g. skin‐of‐colour education to clinicians and patients to address disease‐associated stigma, codevelop study materials including translations) and (iii) retention strategies (e.g. time or travel reimbursement, timely feedback of findings). In phase 4, findings were disseminated to focus group participants. Conclusions Our co‐designed toolkit has the potential to improve ethnic diversity in skin research cohorts to enable more representative findings.